A minimal model of panimmunity maintenance by horizontal gene transfer in the ecological dynamics of bacteria and phages - Wenping Cui; Jemma M. Fendley; Sriram Srikant; Boris I. Shraiman (Proceedings of the National Academy of Sciences, 2025)
Bacteria and phages have been in an ongoing arms race for billions of years. To resist phages bacteria have evolved numerous defense systems, which nevertheless are still overcome by counterdefense mechanisms of specific phages. These defense/counterdefense systems are a major element of microbial genetic diversity and have been demonstrated to propagate between strains by horizontal gene transfer (HGT). It has been proposed that the totality of defense systems found in microbial communities collectively form a distributed “pan-immune” system with individual elements moving between strains via ubiquitous HGT. Here, we formulate a Lotka–Volterra type model of a bacteria/phage community interacting via a combinatorial variety of defense/counterdefense systems and show that HGT enables stable maintenance of diverse defense/counterdefense genes in the microbial pan-genome even when individual microbial strains inevitably undergo extinction. This stability requires the HGT rate to be sufficiently high to ensure that some descendant of a “dying” strain survives, thanks to the immunity acquired through HGT from the community at large, thus establishing a new strain. This mechanism of persistence for the pan-immune gene pool is fundamentally similar to the “island migration” model of ecological diversity, with genes moving between genomes instead of species migrating between islands.